Numerical solutions of 2D Fredholm integral equation of first kind by discretization technique - Khan, Faheem; Arshad, Tayyaba; Ghaffar, Abdul; Sooppy Nisar, Kottakkaran; Kumar, Devendra (AIMS mathematics, 2020)
A novel numerical technique to solve 2D Fredholm integral equations (2DFIEs) of first kind is proposed in this study. This technique is based on the discretization of 2DFIEs by replacing the unknown function with two-dimensional Bernstein polynomial basis functions. We formulate the convergence analysis which shows the fast converges of this technique to the actual solution. Some problems of 2D linear Fredholm integral equations are illustrated to show the efficiency of the proposed scheme.